Review of Randomized Controlled Trials Using e-Health Interventions for Patients With Eating Disorders - Ahmadiankalati, Mojtaba; Steins-Loeber, Sabine; Paslakis, Georgios (Frontiers in Psychiatry, 2020)
Background: Eating disorders (EDs) are highly debilitating conditions. There are high drop out and relapse rates through ED-specific treatments. In a world of technological advancements, electronic devices and services seem to be a promising way to increase patients’ engagement in treatment and to help manage their symptoms. Here, we identified and analyzed the current evidence of RCTs to evaluate the effectiveness and acceptability of e-health interventions in the ED field. Methods: We screened an initial cluster of 581 papers. In the end, 13 RCTs in clinical ED cohorts were included. Results: Some studies were conceived as stand-alone interventions, while others were presented as add-ons to ED-specific treatments. Studies varied in the type of EDs under investigation and in the e-health intervention applied (with vs. without therapist support vs. blended interventions; smartphone- vs. web-based). Only few studies reported explicit acceptability measures. Eight studies reported higher effectiveness of the e-health intervention compared to the control condition, e.g., reduction in maladaptive eating behaviors. Discussion: We identified a big gap in knowledge regarding acceptability and effectiveness of e-health interventions, including lack of studies in older patients, men, sexual and ethnic minorities. Shame/stigma is discussed in the context of e-health interventions for EDs. It remains unclear how severity of EDs affects the effectiveness of e-health interventions, how patients can channel the knowledge they acquire from e-health interventions into their actual behaviors, and how such interventions can better fit the needs of the individual patient to increase acceptability and effectiveness.